In Search of Alternative to Inductionism (K. Popper’s Philosophy of Science) (II) - Nekrašas, Evaldas (Problemos, 1977)
The second part (for the first part see Problemos 19, 1977) of the article considers K. Popper’s pluralistic realism and, in particular, the autonomy of the “third world”. In the article K. Popper’s treatment of the concepts of truth and verisimilitude is discussed. The relation of the philosophical concepts of “late” Popper to logical empiricism and historical school is investigated. The author shows the closeness of Popper’s hypothesism to scepticism and concludes by pointing out eclecticism in Popper’s philosophy of science.